Encyclopedia of Medical Devices and Instrumentation 2006
DOI: 10.1002/0471732877.emd055
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage and Meniscus, Properties of

Abstract: Synovial joints are created to enable movement among articulating bones. During movement, mechanical loading is transmitted across the joint, inducing mechanical stresses among all joint components such as articular cartilage, bone, meniscus, and ligaments. Articular cartilage plays critical roles in enabling motion in the synovial joint. Hyaline is the most common articular cartilage, whereas fibrocartilage is present in the semilunar meniscus of the knee, the temporomandibular joint of the jaw, and the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…SPEU with similar formulation but low HS content presented tensile modulus considerably lower, ranging between 8.5 and 9.8 MPa 59,60 . It has been reported that the circumferential tensile elastic modulus of human meniscus is in the range of 50–198 MPa, 46 while the tensile modulus of human articular cartilage is in the order of 1–30 MPa 33,47 . As the mechanical properties of 3D scaffolds may be lower than their corresponding bulk materials due to their highly porous structure, SPEU50 and SPEU60 could be promising filaments for the preparation of scaffolds for cartilage tissue engineering applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPEU with similar formulation but low HS content presented tensile modulus considerably lower, ranging between 8.5 and 9.8 MPa 59,60 . It has been reported that the circumferential tensile elastic modulus of human meniscus is in the range of 50–198 MPa, 46 while the tensile modulus of human articular cartilage is in the order of 1–30 MPa 33,47 . As the mechanical properties of 3D scaffolds may be lower than their corresponding bulk materials due to their highly porous structure, SPEU50 and SPEU60 could be promising filaments for the preparation of scaffolds for cartilage tissue engineering applications.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, no medical‐grade bioresorbable SPU filaments with high HS content have been reported. These materials are crucial for tissue engineering applications requiring elastomeric materials with high elastic modulus, such as cartilage 46,47 …”
Section: Introductionmentioning
confidence: 99%
“…Cartilage is a smooth elastic tissue, which covers the end of bones at the joints and protects them against mechanical stresses. There are three types of cartilage: articular (hyaline), fibrous, and elastic [38,39]. Heterotypic collagen II/IX/XI fibrils and proteoglycan-glycosaminoglycan networks of aggrecan and hyaluronan are the dominant structures of the cartilage extracellular matrix (ECM).…”
Section: Cartilage Types Properties and Formationmentioning
confidence: 99%